ST2 gene products critically contribute to cellular transformation caused by an oncogenic Ras mutant. Issue 10 (October 2017) - Tago, Kenji; Ohta, Satoshi; Kashiwada, Masaki; Funakoshi-Tago, Megumi; Matsugi, Jitsuhiro; Tominaga, Shin-ichi; Yanagisawa, Ken
Abstract: The ST2 gene was originally identified as a primary responsive gene, and the expressions of its gene products are induced by stimulation with growth factors and by oncogenic stresses. In this study, we observed that oncogenic Ras mutant induced the expression of ST2 and ST2L proteins. Interestingly, the enforced expression of ST2 gene products in NIH-3T3 murine fibroblasts remarkably enhanced Ras (G12V)-induced cellular transformation. Furthermore, when the expression of ST2 gene products was silenced by RNA-interference technique, Ras (G12V)-induced cellular transformation was drastically suppressed. According to these observations, it was indicated that the oncogenic Ras-induced expression of ST2 gene products is required for the acceleration of cellular transformation, and this seems to be independent of the stimulation with IL-33, a ligand for ST2/ST2L. Interestingly, knockdown of ST2 gene products caused a reduction in Rb phosphorylation in transformed murine fibroblasts, suggesting the functional involvement of ST2 gene products in cell cycle progression during cellular transformation. Our current study strongly suggests the importance of ST2 gene products in cellular transformation, and the presence of novel mechanism how ST2 gene products affect the cellular transformation and cell proliferation.